Case Report: Clinical application of hyperbaric oxygen therapy after bladder fistula repair surgery: a report of 7 cases and literature review - Chen, Anjian; Zhu, Han; Liang, Pinyao; Guo, Shanshan; Liang, Tiancai; Zhao, Faliang; Xie, Zhihui; Liang, Guobiao (Frontiers in Surgery, 2025)
Hyperbaric oxygen treatment (HBOT) is a therapeutic modality that delivers 100% oxygen under supra-atmospheric pressure, which has been widely used in the clinical management of various diseases. The incidence of genitourinary fistulas is relatively low in developed countries, mainly presenting as complications of gynecological surgeries, while it remains high in developing nations due to factors such as prolonged labor and inadequate medical care. Among these, bladder fistula is the most common type of genitourinary fistula. This article presents the outcomes of 7 patients who received HBOT after bladder fistula repair surgery, including 6 cases of vesicovaginal fistula (VVF) and 1 case of colovesical fistula (CVF). HBOT was initiated on the first postoperative day, administered once daily for a total of 10 consecutive days, and no relevant adverse reactions occurred in any patient during the HBOT course. All patients achieved uneventful postoperative recovery and were discharged from the hospital, with no recurrence of symptoms observed during the 3–12 months of follow-up. As a novel adjunctive therapy for patients after bladder fistula surgery, HBOT exhibits satisfactory preliminary efficacy and favorable safety profile, yet further research with expanded sample size and in-depth investigation is warranted.